ANALISIS PERHITUNGAN UNIT COST SEWA KAMAR KELAS II AR RAHMAN DENGAN METODE ACTIVITY-BASED COSTING (STUDI KASUS DI RSU PKU MUHAMMADIYAH BANTUL) - Indah Widyasmara; Aris Suparman Wijaya; Mariska Urhmila (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2012)
Background: Determination of unit costs of inpatient room rental in PKU Muhammadiyah Hospital of Bantul is currently using traditional methods of real cost. When viewed in terms of space, design space and facilities for wards between class II class II Ar Rahman with other wards there is a difference. But the room rental unit cost of hospitalization between class II and class II Ar Rahman other similar effect. Methods: The study was conducted in PKU Muhammadiyah Hospital of Bantul. This type of research is a qualitative descriptive case study design. The sample in the study were nurses and managers supporting units taken purposively sampling. Cost analysis method used is the Activity-Based Costing (ABC). Results and Discussion: The unit cost of room rental class II Ar Rahman is calculated by the method of Activity-Based Costing (ABC) amounting to Rp. 77.540, -, while those issued by the hospital of Rp. 42 308, -. This indicates that the unit cost is calculated by Activity-Based Costing is greater than the unit cost hospitals. In Activity-Based Costing (ABC), indirect costs (overheads) charged to a cost driver while in the traditional system is only charged on a cost driver. Conclusions and Suggestions: Method of Activity-based Costing (ABC) can provide information regarding the calculation of more accurate cost, so it can be used by management to take accurate decisions in the budgeting and planning costs. The hospital should conduct an evaluation unit cost for rooms that are used so as not to harm the hospital or the patient.